Classroom Incivility, Gender, Race, and Indigeneity in Higher Education: Faculty Perspectives on Social Factors and Identity Markers - Piquemal, Nathalie; Mahmud, Md. Nazim; Damasceno, Cintia; Heringer, Rebeca (Alberta Journal of Educational Research, 2021)
Based on 20 semi-structured interviews with faculty members from a mid-sized university in Western Canada, this paper offers an examination of research participants’ experiences and perceptions of classroom incivility, particularly those that are shaped by social factors such as identity markers (race, ethnicity, gender) as well as cultural beliefs regarding what is considered politically sensitive subject-matter (in this case, indigeneity). Data analysis reveals that when research participants detect instances of incivility expressed as resentment around race, gender, and indigeneity, they struggle to find a balance between taking up the teaching moment and maintaining safe space. This paper offers a reflection on the extent to which research participants choose to assume intellectual candor when making sense of incivility. Pedagogical responses are highlighted in an effort to recognize the importance of a critical consciousness about social positioning, race relations, power, and privilege. Key words: Incivility, Race, Gender, Indigeneity, Higher Education. Reposant sur 20 entrevues semi-structurées avec des membres du corps professoral d'une université de taille moyenne dans l'Ouest canadien, cet article propose un examen des expériences et des perceptions des participants à la recherche en matière d'incivilité en classe, particulièrement celles qui sont façonnées par des facteurs sociaux tels que les marqueurs d'identité (race, ethnicité, sexe) ainsi que les croyances culturelles concernant ce qui est considéré comme un sujet politiquement sensible (dans ce cas, l'indigénéité). L'analyse des données révèle que lorsque les participants à la recherche détectent des cas d'incivilité exprimés sous forme de ressentiment autour de la race, du genre et de l'indigénéité, ils luttent pour trouver un équilibre entre la prise en charge du moment d'enseignement et le maintien d'un espace sûr. Cet article propose une réflexion sur la mesure dans laquelle les participants à la recherche choisissent d'assumer la franchise intellectuelle lorsqu'ils donnent un sens à l'incivilité. Les réponses pédagogiques sont mises en évidence dans le but de reconnaître l'importance d'une conscience critique du positionnement social, des relations raciales, du pouvoir et des privilèges. Mots clés : incivilité, race, genre, indigénéité, éducation supérieur